1986
DOI: 10.1128/jb.166.3.769-778.1986
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional analysis of beta-lactamase regulation in Bacillus licheniformis

Abstract: The expression of the blaP gene for the ,B-lactamase of Bacillus licheniformis was examined by transcriptional analyses. Radiolabeled probes containing the blaP gene or various regions 3' or 5' to it were used to analyze RNA samples prepared from induced and uninduced cultures of wild-type and mutant B. licheniformis strains.The level of blaP mRNA was low in uninduced wild-type cells. At 37°C, blaP mRNA levels reached a maximum 1 h after induction while rising up to 180-fold and then declined, but remained se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…Bernstein et al (11) reported that T ) 42°C was optimum for -lactamase production, whereas Davies and Abraham (12) reported T ) 30°C. In a more recent study, it was shown that 2-fold more -lactamase was synthesized in cultures grown at 37°C than in cultures grown at 30°C (13). Specific -lactamase activity of cells was shown to be constant irrespective of pH over the range of pH 5.5-7.5.…”
Section: Introductionmentioning
confidence: 97%
“…Bernstein et al (11) reported that T ) 42°C was optimum for -lactamase production, whereas Davies and Abraham (12) reported T ) 30°C. In a more recent study, it was shown that 2-fold more -lactamase was synthesized in cultures grown at 37°C than in cultures grown at 30°C (13). Specific -lactamase activity of cells was shown to be constant irrespective of pH over the range of pH 5.5-7.5.…”
Section: Introductionmentioning
confidence: 97%
“…The rate remains severalfold higher than that of the uninduced culture for 2 or 3 h longer (11). This prolonged induction is not the result of unusual mRNA stability, because the half-life of the ,-lactamase mRNA is only 2 to 3 min (32). Sherratt and Collins reported three possible regulatory loci for the synthesis of 1-lactamase (35).…”
Section: I8-lactamase In B Licheniformis 749mentioning
confidence: 99%
“…This enzyme is a specific hydrolase of β-lactam antibiotics, induced in response to the presence of this class of antibiotic outside the cell (1). BLBlaI is homologous to Staphylococcus aureus BlaI (SABlaI, 126 amino acids) and MecI (SAMecI, 123 amino acids) regulators involved in the induction of BlaZ β-lactamase and resistant penicillin-binding protein 2a (SAPBP2a or SAMecA), respectively (2).…”
Section: Introductionmentioning
confidence: 99%